Infringement of Public Policy and Good Morals as a Ground of Invalidity of Contracts in Private International Law and the Law of the Russian Federation - D. V. Fedchuk (Московский журнал международного права, 2010)
The article describes one of the grounds for rendering contracts invalid – infringement of public policy and good morals, analyses historical development of the terms “public policy” and “good morals” as well as legal regulation of this matter in the international private law, gives recommendations concerning improvement of the Russian legislation.